Elucidation of Enhanced Lithium Conductivity in Nanoporous Ionogel Using Solid State NMR - Mark Weijers; Pranav Karanth; Swapna Ganapathy; Fokko M. Mulder (Advanced Materials Interfaces, 2023)
Abstract Nanostructured solid composite electrolyte or nano‐SCE, which is composed of an ionic liquid, nanoporous silica, and residuals of immobilized precursor components, shows promising synergistic properties. The ionic conductivity of nano‐SCE is in the range of 2–5 mS cm−1, which exceeds the bulk ionic liquid conductivity at ambient temperature, while maintaining characteristics of a solid electrolyte such as having no leakage issues as the ionic liquid is confined, and lower flammability compared to conventional liquid electrolytes. In this study, the underlying mechanism of enhanced conductivity is investigated by using magic angle spinning NMR and NMR relaxometry analysis. Water, one of the volatile precursor molecules has shown to play a key role in the final conductivity and stability at the solid‐electrolyte interface, as it enhances the temperature range in which the ionic liquid remains mobile. In line with previous studies, water with lowered mobility is found in the silicon matrix. The activation energies of lithium ion transfer probed by NMR relaxometry, however, do not change as function of water content. The increase in bulk mobility of lithium ions under ambient conditions compared to water‐less nano‐SCE is found to be the origin of the altered conductivity of this material.